DEPRECIATION AND FUND STATEMENTS. - Zannetos, Zenon S. (The Accounting Review, 1962)
A lot of the arguments concerning the relationship between depreciation and "funds" are due to definitional rather than substantive differences. This article attempts to clarify some major sources of either misconception or trouble that arise in discussions concerning fund statements. Some people wish to use the word "funds" in such a way as to include not only ready cash but also all the classifications included in net working capital, while others use the terms funds and cash as synonymous. There are cases, however, where the difficulty is caused by erroneous assumptions. One of such assumptions is that the undepreciated cost of assets sold is not a source of funds. The author shows that depreciation does not generate funds at the point of sale, no matter how "funds" are defined. However, at the point of production, depreciation generates working capital if it is incorporated into the inventorial product. Since most of the confusion involves issues associated with depreciation, it suggests that a definition of "funds" limited to "cash and cash equivalent" will eliminate a lot of the temptation to elevate mechanics to the status of principles.